PENGARUH SEMANGAT DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT HASJRAT ABADI MANADO - Wuena S.F. Regar; Dantje Keles; Tinneke M. Tumbel (JURNAL ADMINISTRASI BISNIS, 2017)
Abstract. The purpose of this study was to determine the influence of the spirit and discipline on employee productivity at PT. Hasjrat Abadi Manado, either partially or simultaneously. This study uses multiple regression analysis, the independent variables morale (X1) and discipline (X2), and the dependent variable labor productivity (Y). The total sample of 65 respondents, and to test the hypothesis, F test and t test From the analysis of the data obtained the following regression equation: Y = 5.887 + 0.58 X1 + 0.508 X2 + 2. The coefficient of determination (R2) is approximately 0.354 provides that the actual research work productivity can be explained by two independent variables, that is spirit and working discipline at 35.4%. While the remaining 64.6% influenced by other variables not studied. The amount of F count = 18.568> F table = 3.145 with significant level p value = 0.00 <0.05 it can be concluded that Ho refused or Ha accepted which means the spirit and discipline of work affect the productivity of employees. To test t obtained spirit (X1), t = 3,708> t table = 2.042 and significance p value = 0.000> 0.05 it can be concluded that Ho is rejected and Ha accepted, or spirit and discipline effect on employee productivity. Keywords: Spirit, Discipline of Work, Work Productivity